Brief Report: Recent Methamphetamine Use Is Associated With Increased Rectal Mucosal Inflammatory Cytokines, Regardless of HIV-1 Serostatus. (1st May 2018) - Fulcher, Jennifer A.; Shoptaw, Steven; Makgoeng, Solomon B.; Elliott, Julie; Ibarrondo, F. Javier; Ragsdale, Amy; Brookmeyer, Ron; Anton, Peter A.; Gorbach, Pamina M.
Abstract : Background: Methamphetamine use increases the risk of HIV-1 infection among seronegative users and can exacerbate disease progression in HIV-positive users. The biological mechanisms underlying these associations remain unclear. In this cross-sectional pilot study, we examine the associations between recent methamphetamine use and inflammation in the rectal mucosa and peripheral blood compartments in HIV-1 seropositive and seronegative men who have sex with men. Methods: HIV-seronegative and HIV-seropositive men who have sex with men participants were enrolled (N = 24). Recent methamphetamine use was determined by urine drug screen. Cytokines were quantified using multiplex arrays from collected plasma and rectal sponge samples, and peripheral blood T-cell activation was assessed by flow cytometry. Results: Methamphetamine use was associated with consistently increased rectal inflammatory cytokines, specifically interleukin-6 and tumor necrosis factor-alpha, regardless of HIV-1 serostatus in this pilot study. This association was significant after adjusting for age, HIV-serostatus, and receptive anal intercourse frequency using regression analysis. Similar increases were not uniformly observed in peripheral blood. Conclusions: Methamphetamine use is associated with increased local mucosal inflammatory cytokine production. These findings may help explain the increased HIV-1 risk seen in methamphetamine users and contribute to increased inflammation among HIV-seropositive users. Abstract : Supplemental Digital Content is Available in the Text.